(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Digital image authentication is an extremely significant concern for the digital revolution, as it is easy to tamper with any image. In the last few decades, it has been an urgent concern for researchers to ensure the authenticity of digital images. Based on the desired applications, several suitable color image watermarking (CIW) techniques have been developed to mitigate this concern. However, it is tough to achieve a watermarking system that is simultaneously robust and secure. Therefore, this article introduces the hybrid encryption (HE)-based CIW using improved grey-wolf optimizer (IGWO) with least significant bit (LSB) approach, here after denoted as HE with IGWO-LSB. Initially, the HE performed on watermark image to encrypt the data securely before embedding it into cover image. In addition, the IGWO unifies the advantages of traditional GWO with discrete cosine transform (DCT) for enhanced feature extraction in transform domain. Then, LSB approach is employed for embedding the encrypted watermark image into the cover image. Finally, the watermarked image is obtained using IDCT with postprocessing operations. The simulations carried out on standard test images discloses the superiority of proposed HE with IGWO-LSB approach as compared to state-of-art CIW approaches in terms of peak signal-to-noise ratio (PSNR), structural similarity (SSIM) index, mean square error (MSE), normalized cross correlation (NCC) and unified averaged changed intensity (UACI) values.